2019
DOI: 10.1021/acs.biochem.9b00697
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Directly Intercepts DNA Radicals To Inhibit Oxidative DNA–Protein Cross-Linking Induced by the One-Electron Oxidation of Guanine

Abstract: Oxidative DNA damage can lead to cancer, and as enzymatic DNA repair systems become compromised during the aging process, the role of exogenous antioxidants becomes more critical. Here, we examined whether such non-enzymatic DNA repair can be effected by the common cellular antioxidant glutathione, investigating both permanent DNA damage products and the guanine radical intermediates that form them, using the flash-quench technique to carry out the one-electron oxidation of guanine. In gel-shift assays, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This is confirmed in this study by the predominant formation of piperidine‐labile sites and Fpg‐sensitive sites at guanine bases. Furthermore, abundant information is available on the reactivity of Gua • toward several nucleophiles including hydroxide anion (33,34), N3 atom of thymine (46,25), free amino group of polylysine (47–49) and polyamines (50,51). The formation of ICL could be explained by the covalent bond formation between Gua •+ and cytosine or guanine through 4‐ and 2‐amino group, respectively, on the opposite strand.…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed in this study by the predominant formation of piperidine‐labile sites and Fpg‐sensitive sites at guanine bases. Furthermore, abundant information is available on the reactivity of Gua • toward several nucleophiles including hydroxide anion (33,34), N3 atom of thymine (46,25), free amino group of polylysine (47–49) and polyamines (50,51). The formation of ICL could be explained by the covalent bond formation between Gua •+ and cytosine or guanine through 4‐ and 2‐amino group, respectively, on the opposite strand.…”
Section: Resultsmentioning
confidence: 99%
“…When C. sinensis , having a normal GSTO function, is subjected to oxidative stress, CsGSTOs intervene and perform an appropriate role in DNA protection ( Figure 5 C). ROS can directly cause DNA damage, but this can be prevented by GSH [ 40 ]. Here, we describe the as-yet unknown and unique role of GSTO and provide prospects for new ways in which CsGSTOs utilize GSH to protect DNA from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that glutathione (GSH) (0.5–10 mM), the most abundant nonprotein thiol, major antioxidant, and antidote in mammalian cells, plays a vital role in diverse physiological processes involving biocatalysis, protein synthesis, cell metabolism, signal transduction, and maintenance of redox homeostasis, and its abnormal fluctuation may lead to a series of disorders, (e.g., neurological disease, liver damage, and rheumatoid arthritis). Studies have shown that endogenous sulfur dioxide (SO 2 , 0–5 μM) can be produced by GSH and thiosulfate (S 2 O 3 2– ) via thiosulfate sulphurtransferase (TST) in mitochondria, equilibrating with its derivatives sulfite (SO 3 2– )/bisulfite (HSO 3 – ). , By reacting with disulfide bonds of proteins and small molecules, SO 2 takes part in diverse physiological activities, such as regulating cardiac channels, inhibiting myocardial damage, and resisting hypertension. Nevertheless, excess SO 2 may cause damage to respiratory, neurological, cardiovascular, and nervous systems. That is to say, high-dose SO 2 has toxic effects on living organisms, which can be relieved by redox reactions. On the one hand, through the sulfur assimilation pathway, SO 3 2 /HSO 3 – is reduced to S 2– , and Cys is catalyzed by sulfite reductase (SiR) and O-acetylserine lyase (OASTL), respectively.…”
Section: Introductionmentioning
confidence: 99%